2022
DOI: 10.2147/dddt.s373487
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Cyclophosphamide Combined with Prednisone in Membranous Nephropathy Patients with Different Cytochrome P450 2B6 Gene Polymorphisms and Analysis of Factors Influencing the Efficacy

Abstract: Objective To investigate the efficacy of cyclophosphamide combined with prednisone in membranous nephropathy (MN) patients with different cytochrome P450 (CYP) 2B6 gene polymorphisms and explore the factors influencing the efficacy. Methods We performed a prospective and interventional study including 153 outpatients diagnosed with membranous nephropathy from April 2020 to June 2020 in the Bayannur Hospital. Based on the results of CYP2B6 gene polymorphisms, patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The combination of alkylating agents with steroids has demonstrated high efficacy in managing high-risk podocyte-associated proteinuric kidney diseases such as MN ( 151 ). Studies have indicated the effectiveness of the combination of cyclophosphamide with prednisone for various high-risk MN patients ( 152 ). Research indicates that high-dose cyclophosphamide suppresses CD103 + dendritic cells in a rat model, resulting in changes in their frequency, surface molecule expression, and antigen-capturing ability.…”
Section: Therapeutic Strategies Targeting Immunity In Podocyte Injurymentioning
confidence: 99%
“…The combination of alkylating agents with steroids has demonstrated high efficacy in managing high-risk podocyte-associated proteinuric kidney diseases such as MN ( 151 ). Studies have indicated the effectiveness of the combination of cyclophosphamide with prednisone for various high-risk MN patients ( 152 ). Research indicates that high-dose cyclophosphamide suppresses CD103 + dendritic cells in a rat model, resulting in changes in their frequency, surface molecule expression, and antigen-capturing ability.…”
Section: Therapeutic Strategies Targeting Immunity In Podocyte Injurymentioning
confidence: 99%